Improvement of Carded Yarn Quality by Changing Ring Frame Break Draft for Different Short Fibre Index - Md. Riazul Hoque; Md. Rokonuzzaman; Joykrisna Saha; Mohammed Farhad Mahmud Chowdhury (European Scientific Journal, ESJ, 2017)
Three types of cotton fibers lot having short fiber index (SFI) 8.65, 9.45 and 11.00 were taken to perform the experiment. The break drafts (BD) in ring frame were set to 1.136, 1.174 and 1.211 to produce the sample yarn; 30S /1 carded knit yarn (30KK) and 34S /1 carded knit yarn (34KK). The objective of this study was to find out the impact of short fibers by changing ring frame break draft on yarn quality and spinning process performance. The yarn quality such as CVm%, thin places (-50%)/km (TN), thick places (+50%)/km (TK), neps (+200%)/km (NP), count-strength product (CSP) and yarn hairiness (H) found satisfactory level for both yarn count in case of ring frame break draft 1.174 for low and high short fiber index. In this study, both physical and tensile properties of ring yarn were found better for ring frame break draft 1.174 of the three samples and quality deteriorates as SFI increases from 8.65 to 11.00.